Synthesis, crystal structure, and vibrational studies of the monoclinically distorted double perovskite, Sr2Mn1−xNixTeO6 with (x = 0.25, 0.5, and 0.75). (September 2019) - Zaraq, A.; Orayech, B.; Igartua, J. M.; El Bouari, A.
Abstract : The new double perovskite oxides Sr2 Mn1− x Ni x TeO6 with x = 0.25, 0.5 and 0.75 have been synthesized in polycrystalline form by a conventional solid-state reactions process at 1180 °C, in the air. The structural and vibrational properties of these materials were studied by means XRPD, Raman, and IR spectroscopy. It has been proven that all the materials show typical double perovskite structures with a monoclinic symmetry, but with two different space group, P 21 / n for the compositions ( x = 0.25 and 0.5), while the composition ( x = 0.75) crystallizes in the space group I 2/ m . The lattice parameters obtained are in agreement with those of the two pure extremes Sr2 MnTeO6 and Sr2 NiTeO6 . The monoclinic structural distortion involves long range ordering between Te 6+ (in 2 b site) and a random mixture (Mn 2+ /Ni 2+ ) (in 2 a site) for the two compositions ( x = 0.25 and 0.5) that crystallize in P 21 / n . For the material ( x = 0.75) with I 2/ m, similar distortion, ordering and mixing occur at the B and B ' double perovskite sites. It was observed that Vegard Law is satisfied, taking into account the cell parameters of both extremes. The effect of the partial substitution of Mn by Ni was also seen in Raman and IR data where a significant mode shift was observed with nickel content increase.